Acral Dedifferentiated Chondrosarcoma: Report of a Case Arising in the Proximal Phalanx of the Fourth Finger. (December 2021) - Gaeta, Raffaele; Aringhieri, Giacomo; Zampa, Virna; D'Arienzo, Antonio; Andreani, Lorenzo; Capanna, Rodolfo; Zavaglia, Katia; Franchi, Alessandro
Dedifferentiated chondrosarcoma is a well-recognized entity, but its occurrence in the distal extremities is exceedingly rare. We present the case of a 49-year-old woman who experienced local recurrence of an "enchondroma" of the proximal phalanx of the fourth finger of the left hand, which had been initially treated with intralesional curettage at another hospital 4 years before, and 1 year before for a local recurrence. The imaging findings indicated an aggressive behavior, and an incisional biopsy showed a highly cellular proliferation of spindle and pleomorphic elements without evidence of matrix production intermixed with few fragments of a well-differentiated cartilaginous neoplasm with bland cellular atypia, focal nuclear hyperchromatism, and binucleation. An isocitrate dehydrogenase 2 R172S mutation was detected. The final diagnosis was dedifferentiated chondrosarcoma. Despite amputation of the fourth finger, the patient developed lung metastases and further local relapse. Recurrent cartilaginous tumors of the extremities should not be underestimated and should be followed in view of the possible acquisition of aggressive clinical behavior.